A Pure Blue Phosphorescent Organic Light‐Emitting Diode with an External Quantum Efficiency of Over 30% by Using a Tandem Device Architecture. Issue 28 (2nd September 2022) - Chen, Zhao; Tian, Naifan; Tao, Peng; Chen, Shuming; Ma, Dongge; Wang, Lixiang; Wong, Wai‐Yeung
Abstract: Achieving efficient deep blue phosphorescent organic light‐emitting diodes (PHOLEDs) is one of the most difficult and challenging targets nowadays, especially when the Commission Internationale de l'Eclairage (CIE) chromaticity coordinates of y values are smaller than 0.1. Herein, tandem device architectures are fabricated by using an iridium(III) carbene phosphor. In the tandem structures, two electroluminescent units are stacked and connected by a charge generation layer (CGL) which consists of dipyrazino[2, 3‐ f :2′, 3′‐ h ]quinoxaline‐2, 3, 6, 7, 10, 11‐hexacarbonitrile (HATCN) and 4, 4′‐(cyclohexane‐1, 1‐diyl) bis ( N, N ‐di‐ p ‐tolylaniline) (TAPC). Meanwhile, 4, 6‐ bis (3, 5‐di(pyridine‐3‐yl)phenyl)‐2‐methylpyrimidine (B3PYMPM) and diphenyl‐4‐triphenylsilylphenyl phosphine oxide (TSPO1) are used as electron transport layers. The best device gives an external quantum efficiency of 32.3% with the CIE coordinates of (0.15, 0.10), which is among the most efficient blue PHOLEDs made by iridium(III) phosphors. The pure blue emission and high performance are mainly attributed to the efficient and balanced recombination of charge carriers in the two emissive layers, which successfully suppresses the exciplex formation and efficiently confines the triplet excitons. Abstract : Tandem deep blue phosphorescent organic light‐emitting diodes: a tandem device architecture, in which two electroluminescent units are stacked and connected by a charge generation interlayer, is fabricated to achieve a state‐of‐the‐art deep blue phosphorescent organic light‐emitting diode with the Commission Internationale de l'Eclairage chromaticity coordinates of (0.15, 0.10) and external quantum efficiency of 32.3%.